Hemp (Cannabis sativa L.) Varieties: Fatty Acid Profiles and Upgrading of γ‐Linolenic Acid–Containing Hemp Seed Oils - Alonso‐Esteban, José Ignacio; González‐Fernández, María José; Fabrikov, Dmitri; Torija‐Isasa, Esperanza; Sánchez‐Mata, María de Cortes; Guil‐Guerrero, José Luis (European journal of lipid science and technology, 2020)
Hemp seeds (HS) constitute a rich nutrient source and contain γ‐linolenic acid (GLA, 18:3, n‐6), which is a healthy fatty acid (FA). The objectives of this research are i) to look for GLA‐rich varieties of unhusked hemp seeds (UHS) and commercial hulled hemp seeds (HHS); ii) to check the influence of different extracting systems on both oil yield and FA profiles; iii) to test a simultaneous oil extraction/GLA‐enrichment process looking to improve GLA content. Hop and European hackberry seeds (both from Cannabaceae family) are also analyzed for comparative purposes. GLA is the most discriminant FA among UHS varieties, ranging in both UHS and HHS seeds from 0.5% to 4.5% of total FA, while hop seeds are the richest GLA source from Cannabaceae (7.2% of total FA). The extraction system selected for hemp seeds processing has a clear influence on oil yields, although, the FA profiles are slightly modified. The use of n‐hexane and n‐hexane:acetone in extractions allows an improvement in oil yields at the same GLA percentage. A process comprising saponification and subsequent cooling allows the improvement of GLA percentage in both hemp and hop seeds extracts at values higher than 10% of total FA, at high yields (>70%). Practical Applications: The global HS market increases significantly year after year and the demand of hemp products is increasing rapidly. The natural GLA sources in nature are limited, and although hemp contains GLA, this reaches low percentages in the oil. Hemp is a well‐established crop with highly standardized agricultural technologies, thus, the development of any well‐designed processes feasible for application in oil extraction industries, would allow the development of new GLA‐based functional seed oils. This would boost the development of the agricultural and food industries dedicated to revaluing hemp products. In this study, gamma linolenic acid (GLA) occurrence is checked in hemp, hop, and European hackberry seeds. Different extracting systems are checked for oil extraction with the goal to improve GLA content. A process comprising saponification and subsequent cooling allowed improvement in GLA percentage in both hemp and hop seeds extracts at values higher than 10% of total FA, at high yields (>70%).